Quality assurance in dermatopathology: A review of report amendments. (14th September 2020) - Cocks, Margaret; Gru, Alejandro A.
Abstract: Background: Systematic review of amended reports in surgical pathology has been recommended as a valuable exercise in promoting quality assurance and improvement. Examination of report amendments can identify defects in the surgical pathology process and inspire new approaches to decreasing error rates and improving overall patient care. Methods: We performed a retrospective review of all amended dermatopathology reports over a 1.5‐year period at a large academic institution. Results: During the study period, 86 amended reports out of a total 7950 skin‐specific reports were issued (1.08%). Of these amended reports, about 59% (51/86) were because of non‐interpretative errors (eg, wrong site, chin vs shin, etc.) while 41% (35/86) were diagnostic misinterpretations. Of these 35, 24 were considered major diagnostic changes while six were minor. Five amendments provided additional diagnostic information. Of those amended reports with diagnostic misinterpretations, 14/35 involved melanocytic lesions, 8/35 involved non‐melanoma skin cancers or keratinocyte atypia, 10/35 were inflammatory lesions and 3/35 involved other tumors. Conclusion: Our review points to several quality improvement areas that can be targeted to potentially avoid diagnostic errors in dermatopathology, including standardizing certain anatomic sites to prevent misidentification and seeking out clinicopathologic correlation in challenging melanocytic cases.